The identification of biopiracy in patents. (December 2016) - Soria-López, Manuel; Fuentes-Páramo, Israel
Abstract: Evidence on biopiracy of traditional knowledge and biodiversity is scarce. A method for generating evidence from patents was applied to a set of endemic plants used in Mexican Traditional Medicine. First the method identified a sample of patents as a potential source of evidence. Then, relevant arguments obtained from patents and traditional knowledge sources contributed to generate experimental evidence to sustain a possible case of biopiracy. The method's main implication is the possibility of identification of potential evidence on biopiracy by searching the global patent system.